Family-Based Diabetes Self-Management Education terhadap Self Care dan Self-Efficacy - Ramadhani, Dwi Yuniar; Rukmini; Anggraeni, Sindy Maullina; Larasati, Diva Sukma; Intan Elisya; Vidia, Indri (Indonesian Journal of Nursing Research (IJNR), 2024)
Diabetes mellitus is caused by disorders of high blood glucose levels. Lack of self-care and self-efficacy will result in uncontrolled blood sugar levels, causing complications. This research aims to determine the effect of family-based Diabetes Self-Management Education on self-care and self-efficacy in diabetes mellitus sufferers in the Sidotoopo Wetan Region. This research is quantitative research with a Pre-Experimental approach with a one-group pretest Post-test design, with Family Based Diabetes Self-Management Education intervention. The population of elderly people suffering from diabetes mellitus is 30 people, the sample is the entire population, and the sampling technique used is the total population. Data was taken using the SDCSCA and DSMES questionnaires. The statistical tests used are the Wilcoxon test and paired T-test. Research Results show an influence of Family Based Diabetes Self-Management Education on Self-Care and Self-Efficacy with the results of self-care (p value=0.000) and self-efficacy (p value=0.000).Diabetes mellitus sufferers can maintain good self-care and self-efficacy to avoid complications, and the family also plays an important role in maintaining blood sugar stability by supporting and facilitating treatment, monitoring blood sugar, nutritional food consumed, and exercise.   Abstrak Diabetes melitus disebabkan oleh gangguan kadar glukosa darah yang tinggi. Kurangnya perawatan diri dan efikasi diri akan mengakibatkan kadar gula darah tidak terkontrol sehingga menimbulkan komplikasi. Penelitian ini bertujuan untuk mengetahui Pengaruh Pendidikan Self-Management Diabetes Berbasis Keluarga Terhadap Self Care dan Self-Efficacy Pada Penderita Diabetes Mellitus Di Wilayah Sidotoopo Wetan. Penelitian ini merupakan penelitian kuantitatif dengan pendekatan Pre-Experimental dengan desain one-group pretest Post-test, dengan intervensi Family Based Diabetes Self-Management Education. Populasi lansia yang menderita diabetes melitus berjumlah 30 orang, sampelnya adalah seluruh populasi, dan teknik pengambilan sampel yang digunakan adalah total populasi. Data diambil dengan menggunakan kuesioner SDCSCA dan DSMES. Uji statistik yang digunakan adalah uji Wilcoxon dan uji T berpasangan. Hasil Penelitian menunjukkan adanya pengaruh Family Based Diabetes Self-Management Education terhadap Self-Care dan Self-Efficacy dengan hasil perawatan diri (p value=0,000) dan self-eficacy (p value=0,000).Penderita diabetes melitus dapat mempertahankan perawatan diri dan efikasi diri yang baik agar terhindar dari komplikasi, dan keluarga juga berperan penting dalam menjaga kestabilan gula darah dengan mendukung dan memfasilitasi pengobatan, pemantauan gula darah, nutrisi makanan yang dikonsumsi, dan olah raga.